Aluminum based nanostructures for energy applications - Mohammad Tariq Yaseen; Abdalem A. Rasheed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The plasmonic material properties of aluminum allow active plasmon resonances extending from the blue color in the visible range to the ultraviolet (UV) region of the spectrum. Whereas Al is usually avoided for applications of plasmonics due to its losses in the infrared spectrum region. In this work, the study of the scatter and absorption of disk nanoantennas (DNAs) using various types of materials Au, Ag, and Al is accomplished by using the CST microwave studio suite simulation. The results showed that Al can offer good plasmonic properties when DNA radius is 25 nm to 125 nm at 20 nm height and working wavelengths longer than 800 nm in the near-infrared (NIR) region. Al produces negative plasmonic features around 800 nm wavelength due to the interband transition in the imaginary part of epsilon. For Au and Ag, the plasmonic characteristics rapidly decayed when the DNA radius was higher than 60 nm, but in contrast, Al offers good plasmonic features at these large dimensions of DNAs. This extended response of Al in UV, visible, and NIR, incorporated with its low cost, natural abundance, low native oxide, and amenability to industrial processes, could make Al an extremely promising plasmonic metal candidate for energy applications.